Novel client booking system in KLCC Twin Tower bridge - Ameri Mahabadi, H.; Ameri, R. (University of Malaya Press, 2011)
This system should help managing the visitors and tour guides as well as scheduling tours to visit âPetronas Twin Towers Sky Bridgeâ. The system should at least support the following characteristics. It should keep track of visitors and or tourists. It should keep information about tour guides and their working hour and other related information about such employees. The administrators should be able to schedule their visiting hours. This is a work-flow system and it need to keep track of daily visitors. The requirement was meant for this system is straight forward and very clear with so little complexity. On one side the system should provide visitors an online booking interface for them to easily pick their favorite time to visit the place, on the administrative side; it should keep track of visitors and give the ability to admins to manage the timing schedules. This system will replace current working system if it is successful or will add to current existing system to make it more reliable and useful.